Моделюваня впливу монополізму та системи оподаткування на ефективність функціонування економічної системи - Makhort, А. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
Based on the model of an economy with regular interests of consumers, an open economic system with monopolists is investigated. The presence of certain taxation system in the economy is taken into account. The outputs technologies which nonlinearly depend on the output vector are considered for the case of the presence of regular expenditure. For such a mathematical model the optimal solution of the equilibrium problem is presented. The levels of monopolist taxation providing for the realization of the optimal equilibrium state of an economic systems are determined.